How to achieve new progress in ecological civilization construction? – Based on cloud model and coupling coordination degree model - Zhili Zuo (Elsevier, 2021)
Ecological civilization construction (ECC) has become an essential strategy for achieving sustainable development and resolving China's severe resource and environmental issues. Therefore, to understand the current status and spatio-temporal characteristics of China's ECC, this study constructed an indicator system with 23 indicators to investigate China's ECC trends from 2000 to 2019. A cloud model was adopted to obtain the ECC evaluation results. A standard deviational ellipse model was employed to reveal the spatial ECC dynamic evolution process. A coupling coordination degree model was applied to measure the relationship between the ECC and the economy, society, and nature. It was found that: (i) China has not yet fully entered the ecological civilization stage. China’s ECC is slightly higher than the “normal” level, with East China having the highest ECC level; (ii) There is a “gradual” process in the ECC in the six regions, the ECC in 30 Chinese provinces had a generally positive trend from 2000 to 2019; however, the ECC development speed in Northeast China was relatively backward; (iii) The coupling and coordination degree of economy, society, and nature shows significant regional differentiation, with the coast being better than the inland and the south being better than the north. Finally, we put forward policy recommendations to improve the level of China’s ECC from four aspects: narrowing regional differences, strengthening regional cooperation, using scientific and technological means, and increasing ecological culture cultivation.